2015
DOI: 10.5539/jps.v4n2p105
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Plant Height on Fusarium Head Blight in Spring Wheat

Abstract: Fusarium Head Blight (FHB), caused by the fungal species Fusarium graminearum, is a disease affecting wheat cultivars across Canada. Recent and severe outbreaks have spurred research in developing FHB-resistant cultivars and evaluating the underlying causes of FHB susceptibility. In this study, the effect of plant height on Fusarium Head Blight in Canadian spring wheat was evaluated over a two-year period. Cultivars of spring wheat varying in origin, height, and disease susceptibility were artificially inocula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…This FHB resistance experiment demonstrated that the ECAD lines showed moderate resistance to fusarium spores and performed very well compared to the checks. A negative correlation was observed between plant height and FHB morbidity which is similar to a previous study reported by Moidu et al (2015). In addition, race 77-2 TJBJ showed the highest damage to wheat leaves among all LR races in the LR inoculation test, similar to what was reported by Chen et al (2015).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This FHB resistance experiment demonstrated that the ECAD lines showed moderate resistance to fusarium spores and performed very well compared to the checks. A negative correlation was observed between plant height and FHB morbidity which is similar to a previous study reported by Moidu et al (2015). In addition, race 77-2 TJBJ showed the highest damage to wheat leaves among all LR races in the LR inoculation test, similar to what was reported by Chen et al (2015).…”
Section: Discussionsupporting
confidence: 90%
“…Every year, scientists use many methods to examine the wheat genome in hopes of identifying the gene segment that confers FHB resistance (Buerstmayr, Ban & Anderson, 2009). Unfortunately, there have been no explicit results yet, but some correlation between plant height and FHB severity has been reported (Moidu et al, 2015). In addition, F. graminearum, leads to high concentrations of deoxynivalenol (DON) in wheat kernels, a mycotoxin known to be harmful to humans (Xue, 2012).…”
Section: Introductionmentioning
confidence: 99%